Proteome changes in the plasma of myelodysplastic syndrome patients with refractory anemia with excess blasts subtype 2 - Majek, Pavel; Riedelova-Reicheltova, Zuzana; Suttnar, Jiri; Pecankova, Klara; Cermak, Jaroslav; Dyr, Jan E (Disease markers, 2014)
The goal of this study was to explore the plasma proteome of myelodysplastic syndrome (MDS) patients with refractory anemia with excess blasts subtype 2 (RAEB-2) in comparison to healthy controls. 20 plasma samples were separated with 2D electrophoresis and statistically processed with Progenesis SameSpots software. 47 significantly differing (P < 0.05) spots were observed, and 27 different proteins were identified by nano-LC-MS/MS. Mass spectrometry-based relative label-free quantification showed a 2-fold increase of the leucine-rich alpha-2-glycoprotein (LRAG) peptide levels in the RAEB-2 group. Changes in the fragments of the inter-alpha-trypsin inhibitor heavy chain H4 (ITIH4) protein were observed. Western blot analysis showed no differences in albumin and ITIH4 levels, while increased expression was observed for LRAG in the RAEB-2 group. Quantification using ELISA showed decreased plasma level of alpha-2-HS glycoprotein in the RAEB-2 group. In conclusion, this is the first time that alpha-2-HS glycoprotein and LRAG were proposed as new biomarkers of RAEB-2 and advanced MDS, respectively. Alpha-2-HS glycoprotein, a protein involved in the bone marrow development and previously proposed as a MDS biomarker candidate, was significantly decreased in RAEB-2. Increased expression and changes in modification(s) were observed for LRAG, a protein involved in granulocytic and neutrophil differentiation, and angiogenesis.
Keywords: dospělí; Female; biologické markery; proteom; Biomarkers; Adult; mladý dospělý; ženské pohlaví; Tandem Mass Spectrometry; sekvence aminokyselin; Proteome; lidé; studie případů a kontrol; Amino Acid Sequence; peptidové fragmenty; Blood Proteins; Myelodysplastic Syndromes; krevní proteiny; myelodysplastické syndromy; Anemia, Refractory, with Excess of Blasts; Male; tandemová hmotnostní spektrometrie; Case-Control Studies; Aged; Peptide Fragments; anotace sekvence; Young Adult; Molecular Sequence Annotation; lidé středního věku; senioři; mužské pohlaví; Middle Aged; refrakterní anemie s nadbytkem blastů; Humans